Performance Evaluation of Spectrum Sensing and RF Energy Harvesting for Cognitive Radios based on SDR - Singh, Supreet (Thapar University, 2017)
Cognitive Radio (CR) presents a lot of challenges to develop the techniques and methodologies to dynamically utilize the unused or underused spectrum. Spectrum sensing is identified as a very important task upon which the entire operation of cognitive radio depends.The issue of efficient utilization of radio re- sources can be implemented unitedly through dynamic waveform design and an efficient spectrum sensing. In this research work, waveform design using Spec- trally Modulated Spectrally Encoded (SMSE) framework is conjoined with the Cyclostationary based Sensing technique (CSS) for CR. We take a simple sys- tem model in which one Primary transmitter communicates with one Primary Receiver and one Secondary transmitter with one Secondary Receiver in an interweave manner. In order to identify the free spectrum, an analytical ex- pression of waveform design variables in terms of sensing parameters has been derived. Further, to find the channel occupancy/spectrum holes, a new joint CSS and SMSE based test metric has been proposed. The joint test stat offers a better and clear decision by providing a large gap between test stat and the required threshold setting. In particular, we combine the flexibility (dynamic channel allocation and dynamic waveform design) provided by SMSE frame- work and sensitivity (ability to deal with the weak signals) provided by CSS to improve the accuracy of the final decision of spectrum sensing. To evaluate the receiver performance, receiver operating characteristic (ROC) curves have been plotted which show that the proposed joint scheme achieves a significant performance improvement at lower SNR values when compared with tradition- ally available detectors. The spectrum sensing and proposed scheme is then extended in a multiple antenna scenario with maximal ratio combining used at the secondary transceiver. From the deployment point of view and to increase the spatial distance of SU communication, co-operative two way relay communication is a powerful tool for CR. Due to certain observations, the previously proposed system model is modified to include the cognitive relay based SU communication. However, ii in many practical scenarios, the relay may consist of a battery powered de- vice operating under energy constraints. Thus, for prolonging the lifetime of a relay device in wireless network, energy harvesting (EH) from RF signal has received much greater attention recently. Therefore, the performance of energy harvesting (EH) relay based Interweave/Underlay Cognitive Radio Net- work is investigated. We employ Amplify and forward (AF) relay technique along with Time-switching relaying protocol (TSR) for energy harvesting at the cognitive relay. Based on sensing accuracy, we derive an expression for op- timization of charging duration TSR parameter and sensing duration for maxi- mizing throughput of interweave Cognitive Radio. Based on sensing efficiency, throughput and outage probability for underlay CR is analyzed considering the interference temperature constraints and optimal power distribution parame- ter at secondary user (SU) terminals. Variations in the sum-rate and detection probability are considered in terms of CDF of the terminal SNRs. We prove that erogodic sum-rate is maximized in underlay CR case, when interference power distribution parameter is half across the SU terminals. The optimized values of switching-time ratios have been derived analytically for both Interweave and Underlay CR. The results thus obtained are compared by taking symmetrical and asymmetric channels between SU terminals. Analytical results are also val- idated through monte-carlo simulations to confirm the accuracy of the derived expressions. ii
Keywords: cognitive Radio; Spectrum sensing; Energy harvesting; SMSE framework; Hybrid CR